2005
DOI: 10.1002/lt.20587
|View full text |Cite
|
Sign up to set email alerts
|

Current role of liver transplantation for the treatment of urea cycle disorders: A review of the worldwide English literature and 13 cases at Kyoto University

Abstract: To address the current role of liver transplantation (LT) for urea cycle disorders (UCDs), we reviewed the worldwide English literature on the outcomes of LT for UCD as well as 13 of our own cases of living donor liver transplantation (LDLT) for UCD. The total number of cases was 51, including our 13 cases. The overall cumulative patient survival rate is presumed to be more than 90% at 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
106
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 39 publications
3
106
0
3
Order By: Relevance
“…When an OTCD diagnosis is known prior to the birth of the child, prospective treatment has been successful [5]. Recent studies have suggested a role for liver transplantation in the management of severe OTCD [6][7][8][9][10] although long-term data are not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…When an OTCD diagnosis is known prior to the birth of the child, prospective treatment has been successful [5]. Recent studies have suggested a role for liver transplantation in the management of severe OTCD [6][7][8][9][10] although long-term data are not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, as patients with IEM have a low incidence of comorbid disease, they might be expected to have better long-term survival than patients with other diseases like chronic hepatitis who are at risk of numerous extra-hepatic morbidities or recurrence of the primary liver disease (e.g., hepatitis C where graft recurrence is almost universal). Indeed, patient survival in large series patients with UCD undergoing liver transplantation was significantly higher than in patients undergoing liver transplantation for other reasons at that same center (Morioka et al 2005). Age and need for life support are two powerful predictors of survival after liver transplantation (Dutkowski et al 2011) and patients with IEM are likely to be younger, to be stable between episodes of decompensation, and to have fewer comorbid diseases than patients with end-stage liver disease or cancer and thus might be predicted to have improved survival after receiving liver transplantation relative to those with other diseases such as chronic hepatitis or hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of evidence on therapy outcomes -there are no systematic studies available which assess the efficacy of transplantation in adults with IEM. Adults are included in many case series (for example, see Morioka et al 2005;Summar et al 2005;Mazariegos et al 2012) and there is not a suggestion in these series that the outcomes are worse for the adults than for the children but data are not analyzed separately to make that determination. Such analysis is required as the risks of transplantation in adults (who have comorbid disease) will differ from those in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 As shown in several studies, 5-year survival rates are greater than 85% with transplant. [4][5][6] Liver transplant during the first few months of life may prevent neurologic deficits in severe cases. However, transplant at early ages also may increase the risk of perioperative and postoperative complications.…”
Section: Introductionmentioning
confidence: 99%